Design and control technique for single phase bipolar H-bridge inverter connected to the grid - Linda Hassaine; Mohamed Rida Bengourina (Institute of Advanced Engineering and Science, 2020)
The power quality injected into the grid and the performance of the converter system depend on the quality of the inverter current control. This paper proposes a design and control technique for a photovoltaic inverter connected to the grid based on the digital pulse-width modulation (DSPWM) which can synchronise a sinusoidal output current with a grid voltage and control a power factor. The current injected must be sinusoidal with reduced harmonic distortion. The connected PV system is based on H-Bridge inverter controlled by bipolar PWM Switching. The current control technique and functional structure of this system are presented and simulated. Detailed analysis, Simulations results of output voltage and current waveform demonstrate the contribution of this approach to determinate the suitable control of the system. A digital design of a generator PWM using VHDL is proposed and implemented on an Xilinx FPGA and it has been validated with experimental results. As a result, the proposed inverter implementation is simple, and it becomes an attractive solution for low power grid connected applications.